Integrated tunable laser controlled by nano-silicon-photonic circuits - Ren, Min (2015)
This doctorate thesis focuses on the design, fabrication and experimental characterization of integrated external cavity tunable lasers realized via nano-silicon-photonic (NSP) integrated circuits. Specifically, the laser system is constructed by linear or ring external cavity configuration and tuned using thermal-optic, free-carrier injection and opto-mechanical approaches. An external cavity tunable laser, controlled by electrical approaches, is demonstrated, which integrates a gain chip and external NSP integrated circuits onto a silicon-on-isolator platform. A coupled ring resonator structure serves as a wavelength selective reflector. The wavelength is electrically tuned by changing the effective refractive index of the ring waveguide, via both thermal-optic and free-carrier effects, to obtain an over 40-nm tuning range and 2-pm tuning accuracy. Next, an external cavity laser controlled by an opto-mechanical approach, instead of the electrical approach, is reported. The lasing wavelength is optically tunable by controlling the deflection of the ring waveguide in the external PIC, getting rid of the problems caused by the electrical tuning approach.Third, a ring cavity tunable laser, integrated by NSP circuits and formed in a closed-loop cavity, is demonstrated. It consists of a semiconductor optical amplifier chip, two separated ring resonators and a novel U-shape sub-loop waveguide circuit that enables unidirectional light operation in the ring-cavity. A 50-dB side mode suppression ratio within a 50-nm tuning range is obtained in the experiments. The successful implementation of three different tunable lasers has evidenced the effectiveness of employing NSP integrated circuits in external cavity tunable lasers to improve the specifications and performances.